Cozzy Bun Cafe & Bakery / Aubery D. A David ... [et al.] - David, Aubery D. A; Shamsul, Ahmad Sufyan; Ruslan, Dayang Ardila Wati; Abd Rahman, Dg Seri Rahmah (2011)
The name of our company is Cozzy, while the name of our business is Cozzy Bun Cafe & Bakery. Our business focuses on trading whereby our product more on buns, cakes and beverages. Therefore our industry is focuses on retailing. The location of our business is Lot 40, Third Floor of Suria Sabah, Kota Kinabalu. The reason we choose this kind of business is because the location is strategic place for the customer to look for food and beverages. Most of our members interested in this industry. For our market customer, we assume that local people and tourist will come to our premise to purchase our products. Therefore, in future we hope that the product of our company can be export outside of Sabah in hope of expanding our market to the nationwide. According to Department of Statistics Malaysia 2011, there will be 3 120 040 tourist come to Malaysia. Therefore, we assume that many people consists of local people and tourist will become our customer and gain more profit.